Prevalence of Growth Disorders in a Nationally Representative Sample of Iranian Adolescents According to Socioeconomic Status: The CASPIAN-III Study - Maryam Bahreynian; Mohammad Esmaeil Motlagh; Mostafa Qorbani; Ramin Heshmat; Gelayol Ardalan; Roya Kelishadi (Elsevier, 2015)
This study aims to assess the prevalence of growth disorders among a nationally representative sample of Iranian adolescents according to the socioeconomic status (SES) of their living area. Methods: This nationwide cross-sectional survey was conducted among a representative sample of 5624 adolescents aged 10-18 years. They were selected by multistage cluster sampling from 27 provinces of Iran. Subnational classification of the country was based on geography and social class of each region. Analysis of variance and Chi-square tests were used to compare the prevalence of growth disorders according to sex and SES of the living regions. Results: The mean and standard deviation for body mass index was 19.42 (4.09) kg/m2, with a significant trend from the Southeast region with lowest SES to the Central part with highest SES (ptrend < 0.001). The prevalence of obesity, combined overweight and obesity, as well as abdominal adiposity increased with a significant trend from low to high SES (all ptrend < 0.001, except for girls' height, ptrend = 0.003). The opposite direction was documented for the prevalence of underweight and short stature, with the highest frequencies in the Southeast (lowest SES) and the lowest in Central part (highest SES). Conclusion: Excess weight was more prevalent in high SES regions, whereas underweight and short stature were more prevalent in low SES regions. These findings underscore the necessity of implementing evidence-based health promotion programs and preventive strategies according to SES.